Factors affecting higher education students’ behavioral intention toward hybrid learning in Malaysian private universities - Chen, Chee Heng; Lee, Wen Chye; Ng, Kok Seng; Ngeau, Jiun Yuan (2022)
The standard pedagogical method can be improved with hybrid learning, which serves as a flexible tool to aid students in higher education in their learning. Since the Covid-19 epidemic, hybrid learning has emerged as a fast-expanding educational trend in Malaysia's educational paradigm, and it is becoming one of the essential learning modes for students at the higher education level. The importance of behavioural intention toward hybrid learning is recognized and played as the fundamental purpose of the current research. The primary purpose of conducting this research is to examine whether the six variables: perceived usefulness of hybrid learning system (PU), perceived ease of use (PE), internet access (IA), self-efficacy (SE), teacher support (TS), and campus support (CS) will influence the higher education students’ behavioural intention toward hybrid learning in Malaysian private universities. This research was conducted, and questionnaires were distributed to 500 respondents in 8 selected private universities located in Kuala Lumpur, Negeri Sembilan, Perak, and Selangor, with 500 responses well received. Reliability and Multiple Linear Regression analysis were used to test the research model. The findings manifest that PU, PE, IA, and TS are found to have a significant influence on higher education students’ behavioural intention toward hybrid learning. Besides, this research provides implications for institutions and future researches to understand the factors affecting higher education students’ behavioural intention toward hybrid learning in Malaysian private universities. Several recommendations are also highlighted for future researches so that the potential area of improvement can be further justified.